2015
DOI: 10.1002/2015gl065129
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Hall physics in magnetic reconnection due to cold ions at the Earth's magnetopause

Abstract: Magnetic reconnection is a process permitting mass and energy exchange across plasma boundaries and converting magnetic energy into particle kinetic energy. Strong electric fields and currents due to the Hall effect are set up in narrow regions where ions are demagnetized but electrons remain magnetized. It has been recently shown that cold (few eV) ions are abundant or even dominate the Earth's magnetosphere, but most of the previous reconnection studies do not account for this population. These cold ions rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 50 publications
7
81
0
Order By: Relevance
“…In addition, cold ions have a smaller gyroradius than hot ions and introduce a new length-scale Toledo-Redondo et al, 2015]. However, the rapid cold ion heating observed for event 2, which occurs right before the narrow structure of increased E n predicted by simulations [Pritchett, 2008;Pritchett and Mozer, 2009] and confirmed by observations [Khotyaintsev et al, 2006;André et al, 2010], has implications for the current reduction observed by Toledo-Redondo et al [2015]. However, the rapid cold ion heating observed for event 2, which occurs right before the narrow structure of increased E n predicted by simulations [Pritchett, 2008;Pritchett and Mozer, 2009] and confirmed by observations [Khotyaintsev et al, 2006;André et al, 2010], has implications for the current reduction observed by Toledo-Redondo et al [2015].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cold ions have a smaller gyroradius than hot ions and introduce a new length-scale Toledo-Redondo et al, 2015]. However, the rapid cold ion heating observed for event 2, which occurs right before the narrow structure of increased E n predicted by simulations [Pritchett, 2008;Pritchett and Mozer, 2009] and confirmed by observations [Khotyaintsev et al, 2006;André et al, 2010], has implications for the current reduction observed by Toledo-Redondo et al [2015]. However, the rapid cold ion heating observed for event 2, which occurs right before the narrow structure of increased E n predicted by simulations [Pritchett, 2008;Pritchett and Mozer, 2009] and confirmed by observations [Khotyaintsev et al, 2006;André et al, 2010], has implications for the current reduction observed by Toledo-Redondo et al [2015].…”
Section: Discussionmentioning
confidence: 99%
“…The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015]. The first encounter (event 1) was previously discussed by ; Graham et al [2015] and Wang et al [2015], and the second encounter (event 2) was previously discussed by Lee et al [2015] and Toledo-Redondo et al [2015].…”
Section: Events Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This velocity change also affects the rate of energy conversion in magnetic reconnection. Low-energy ions also change how the microphysics of magnetic reconnection works since the gyro-radius introduces a new length-scale between the gyro-radii of electrons and hot ions (André et al 2010, Toledo-Redondo et al 2015.…”
Section: Low-energy Ions and A Better Map Of Near-earth Spacementioning
confidence: 99%
“…If there are indeed cold ions in the plasma sheet, the polar wind would be one of the major suspects for the source, next to plasmaspheric winds and plumes. Toledo-Redondo et al (2015) recently found, while studying reconnection at the dayside magnetopause, that cold ions introduce a new length scale in the reconnection process and thus may affect it.…”
Section: Introductionmentioning
confidence: 99%